The Invisible Hand of Partisan Irrationality - Licon , Jimmy (2025)
Why do we vote, protest, and boycott? Economists explain partisan actions, despite their costs, by arguing political irrationality by a single partisan isn’t costly to them as an individual - they can afford the political irrationality, despite the social costs. And some philosophers worry about the moral and epistemic costs of political irrationality. Here I argue that political irrationality has some benefits: it encourages partisans to engage in virtue signaling and rationalization in politics. And while virtue signaling and rationalization are often epistemically and morally bad, they can nonetheless confer benefits too, like facilitating societal and moral progress.